How general are positive relationships between plant population size, fitness and genetic variation? - Leimu, R; Mutikainen, P; Koricheva, J; Fischer, M (2006)
Relationships between plant population size, fitness and within-population genetic diversity are fundamental for plant ecology, evolution and conservation. We conducted meta-analyses of studies published between 1987 and 2005 to test whether these relationships are generally positive, whether they are sensitive to methodological differences among studies, whether they differ between species of different life span, mating system or rarity and whether they depend on the size ranges of the studied populations. 2 Mean correlations between population size, fitness and genetic variation were all significantly positive. The positive correlation between population size and female fitness tended to be stronger in field studies than in common garden studies, and the positive correlation between genetic variation and fitness was significantly stronger in DNA than in isoenzyme studies. 3 The strength and direction of correlations between population size, fitness and genetic variation were independent of plant life span and the size range of the studied populations. The mean correlations tended to be stronger for the rare species than for common species. 4 Expected heterozygosity, the number of alleles and the number or proportion of polymorphic loci significantly increased with population size, but the level of inbreeding FIS was independent of population size. The positive relationship between population size and the number of alleles and the number or proportion of polymorphic loci was stronger in self-incompatible than in self-compatible species. Furthermore, fitness and genetic variation were positively correlated in self-incompatible species, but independent of each other in self-compatible species. 5 The close relationships between population size, genetic variation and fitness suggest that population size should always be taken into account in multipopulation studies of plant fitness or genetic variation. 6 The observed generality of the positive relationships between population size, plant fitness and genetic diversity implies that the negative effects of habitat fragmentation on plant fitness and genetic variation are common. Moreover, the stronger positive associations observed in self-incompatible species and to some degree in rare species, suggest that these species are most prone to the negative effects of habitat fragmentation. © 2006 The Authors.